Stories of Friendship: The Generous Contributions of Paul Wadell - Charles Pinches (Journal of Moral Theology, 2021)
This paper reviews and appreciates the contributions of Paul Wadell to the field of moral theology. It suggests connections between Wadell’s writing on Aquinas and on friendship and notes a progression in his work on friendship beginning with natural friendship and moving towards Christian friendship. It argues for a distinctiveness in friendship that distinguishes it from other loves and so makes it especially formative of moral character and, following Aristotle, open to political life.